2020
DOI: 10.1016/j.jcmgh.2020.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 27 Protects From Gastric Atrophy and Metaplasia During Chronic Autoimmune Gastritis

Abstract: Background & Aims The association between chronic inflammation and gastric carcinogenesis is well established, but it is not clear how immune cells and cytokines regulate this process. We investigated the role of interleukin 27 (IL27) in the development of gastric atrophy, hyperplasia, and metaplasia (preneoplastic lesions associated with inflammation-induced gastric cancer) in mice with autoimmune gastritis. Methods We performed studies with TxA23 mice (control mice), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…In the CTLA4 insufficiency model, treatment with anti-IL4-antibody and knockout of IL4Rα did not prevent inflammation but severed its link with the initiation of tumorigenesis ( Miska et al, 2018 ), suggesting that therapies targeting type 2 inflammation may be useful in promoting anti-cancer immunity or cancer prevention as well. This idea could be further supported by other models of gastric injury which have found that ILC2s are key mediators of a metaplastic response or that administration of IL27, an inhibitor of type 2 and other types of immunity ( Yoshida and Hunter, 2015 ; Tait Wojno et al, 2019 ), protects against metaplasia ( Bockerstett et al, 2020 ; Meyer et al, 2020 ).…”
Section: Type 2 Inflammatory Pathways Unveiled In Studies Of Autoimmune Tumorigenesis May Provide New Targets To Improve Cancer Immune Thmentioning
confidence: 79%
See 1 more Smart Citation
“…In the CTLA4 insufficiency model, treatment with anti-IL4-antibody and knockout of IL4Rα did not prevent inflammation but severed its link with the initiation of tumorigenesis ( Miska et al, 2018 ), suggesting that therapies targeting type 2 inflammation may be useful in promoting anti-cancer immunity or cancer prevention as well. This idea could be further supported by other models of gastric injury which have found that ILC2s are key mediators of a metaplastic response or that administration of IL27, an inhibitor of type 2 and other types of immunity ( Yoshida and Hunter, 2015 ; Tait Wojno et al, 2019 ), protects against metaplasia ( Bockerstett et al, 2020 ; Meyer et al, 2020 ).…”
Section: Type 2 Inflammatory Pathways Unveiled In Studies Of Autoimmune Tumorigenesis May Provide New Targets To Improve Cancer Immune Thmentioning
confidence: 79%
“…This condition has been modeled in mice, which undergo epithelial transformation to gastric metaplasia ( Nguyen et al, 2013 ). This model has suggested a link between autoimmunity and tumorigenesis, where administration of IL27, which may inhibit all three types of immunity ( Yoshida and Hunter, 2015 ; Tait Wojno et al, 2019 ), blocked the formation of metaplasia ( Bockerstett et al, 2020 ). The idea that type 2 inflammation induces epithelial transformation has been confirmed in an animal model system mimicking human CTLA4 insufficiency.…”
Section: Ctla4 Insufficiency and Other Models Of Autoimmune Gastritis Provide Experimental Evidence Of Autoimmunity-driven Tumorigenesismentioning
confidence: 99%
“…4,[9][10][11][12] In contrast, disruption of cytokines that exert anti-inflammatory effects, such as IL10 or IL27, may increase cancer risk. [13][14][15] Recent studies by our group have uncovered the broad anti-inflammatory role of the steroid hormones glucocorticoids and androgens within the stomach. 16,17 Loss of these hormones leads to spontaneous activation of the innate immune response, driving SPEM development.…”
mentioning
confidence: 99%
“…In a prospective study, women who developed AIG were found to have T cell and macrophage infiltration in their stomach biopsies as well as increased HLA-DR (MHC II) expression on epithelial cells (Burman et al, 1992). Mast cells and eosinophils have also been identified in the setting of AIG, but their contribution to disease and the significance of infiltration have not yet been determined (Park et al, 2013;Bockerstett et al, 2020).…”
Section: Autoimmune Gastritismentioning
confidence: 99%